(untitled) - Weinberger, David (Boston, Massachusetts, 2019)
Modern science, the Internet, big data, and AI are each saying the same thing to us: the world is -- and always has been -- far more complex and unpredictable than we've allowed ourselves to see. As a result we're undergoing a sea change in our understanding of how things happen, and in our deepest strategies for predicting, preparing for, and managing our lives and our businesses. For example, machine learning allows us to make better predictions (think the weather, stock performance, online clicks) but we know less about why those predictions are right--and we need to get used to that. And in fact, over the past twenty years we've been unintentionally developing strategies that avoid anticipating what will happen so we don't have to depend on unreliable revenue forecasts, assumptions about customer needs, and hypotheses about how a product will be used. By embracing these strategies, we're flourishing by creating yet more possibilities and yet more unpredictability.
Keywords: Đổi mới công nghệ,Technological innovations